(untitled) (Práxis Educativa, 2025)
Intervening in executive processes such as planning, working memory, and inhibition in children from vulnerable backgrounds, using pedagogical and ecological strategies, may enhance intellectual abilities and personality development. A quantitative study was conducted with a pre-test sample of 102 students and a post-test sample of 64 children aged 8 to 10. The Banfe-3, K-BIT, and CPQ instruments were applied. The results revealed significant improvements in executive functioning, intellectual capacity, and personality regulation among children in a vulnerable institution. Executive functioning improved from mild impairment to low-normal levels, IQ increased from low average to average, and personality traits showed better anxiety regulation, reduced extroversion, and normalized psychoticism. These findings suggest that it is possible to enhance executive performance, intellectual skills, and emotional and behavioral regulation in children from vulnerable contexts, even when adverse conditions persist. Keywords: Executive functions. Intelligence. Personality. Childhood. Vulnerability.